Sodium ferric pyrophosphate positive electrode material as well as preparation method and application thereof

The NFPP positive electrode material prepared by the two-fluid spray drying method solves the problems of large particle size and high porosity of the existing materials, and achieves higher compaction density and battery performance.

CN119674059APending Publication Date: 2025-03-21NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411850524.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing sodium ferric pyrophosphate (NFPP) cathode material has a large particle size and high internal porosity, resulting in a decrease in compaction density, affecting battery capacity, internal resistance and processing difficulty, and poor circulation and rate performance.

Method used

The NFPP positive electrode material was prepared by the two-fluid spray drying method, and the particle size was controlled to be between 2-10 μm, the internal porosity was less than 14%, and the compaction density was increased by sintering treatment.

Benefits of technology

The compaction density of NFPP positive electrode material is improved, its capacity, circulation performance and rate performance are improved, internal porosity is reduced, and the overall performance of the battery is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674059A_ABST
    Figure CN119674059A_ABST
Patent Text Reader

Abstract

The invention provides a ferric sodium pyrophosphate positive electrode material as well as a preparation method and application thereof. The D50 of the sodium ferric phosphate pyrophosphate positive electrode material is 2-10 [mu] m, and the maximum particle size of the sodium ferric phosphate pyrophosphate positive electrode material is less than 25 [mu] m; the internal porosity of the ferric sodium pyrophosphate positive electrode material is less than 14%, and the compaction density is greater than 2.17 g / cm < 3 >. According to the invention, the compaction density of the ferric sodium pyrophosphate positive electrode material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a sodium iron phosphate pyrophosphate positive electrode material and a preparation method and application thereof, belonging to the technical field of positive electrode materials for sodium ion batteries. Background Art

[0002] Sodium-ion batteries have great development prospects in the energy storage market. Positive electrode materials (such as sodium iron phosphate pyrophosphate positive electrode materials) are one of the important components of sodium-ion batteries. Sodium iron phosphate pyrophosphate (Na4Fe3(PO4)2(P2O7), NFPP) has a high specific capacity of 129mAhg It is considered to be the most competitive positive electrode material in electrochemical energy storage batteries due to its advantages such as stable structural cycle, long life and low production cost.

[0003] Spray drying combined with carbon thermal reduction is a mainstream method for synthesizing NFPP at low cost and on a large scale. However, the cathode material (such as NFPP) prepared by this method has large particle size and high internal porosity of the particles. The large particle size and high internal porosity of the cathode material will lead to a decrease in the compaction density of the cathode material, which will directly affect the battery capacity, internal resistance and processing difficulty. The internal porosity of the cathode material is high, and the side reactions that occur therein are more violent, resulting in poor cycle performance; and under high-rate charging, the cathode material may also have sodium deposition problems. Summary of the invention

[0004] The present invention provides a sodium iron phosphate pyrophosphate positive electrode material and a preparation method and application thereof. The sodium iron phosphate pyrophosphate positive electrode material has a small particle size and a small internal porosity, which helps to increase the compaction density of the sodium iron phosphate pyrophosphate positive electrode material and improve its capacity (specific capacity, energy density), cycle performance and rate performance.

[0005] The present invention provides a sodium iron phosphate pyrophosphate positive electrode material, wherein the D50 of the sodium iron phosphate pyrophosphate positive electrode material is 2-10 μm, and the D100 of the sodium iron phosphate pyrophosphate positive electrode material is less than 25 μm; the internal porosity of the sodium iron phosphate pyrophosphate positive electrode material is less than 14%, and the compaction density is greater than 2.17 g / cm 3 .

[0006] Optionally, there are m peaks in the particle size distribution diagram of the sodium iron phosphate pyrophosphate positive electrode material, and the peak intensities of the sodium iron phosphate pyrophosphate positive electrode material corresponding to the m peaks are not equal, wherein m is an integer greater than or equal to 2.

[0007] Optionally, among the m peaks, at least one peak corresponds to the peak intensity of the sodium iron phosphate pyrophosphate positive electrode material of 1~4μm, and the mass ratio of the sodium iron phosphate pyrophosphate positive electrode material with a peak intensity of 1~4μm to the sodium iron phosphate pyrophosphate positive electrode material is 10~50%; at least one peak corresponds to the peak intensity of the sodium iron phosphate pyrophosphate positive electrode material of 6~10μm.

[0008] Optionally, when m is 2, the peak intensity of the sodium iron phosphate pyrophosphate positive electrode material corresponding to one of the peaks is 1~4μm, and the mass ratio of the sodium iron phosphate pyrophosphate positive electrode material with a peak intensity of 1~4μm to the sodium iron phosphate pyrophosphate positive electrode material is 10%~50%; the peak intensity of the sodium iron phosphate pyrophosphate positive electrode material corresponding to another peak is 6~10μm, and the mass ratio of the sodium iron phosphate pyrophosphate positive electrode material with a peak intensity of 6~10μm to the sodium iron phosphate pyrophosphate positive electrode material is 50%~90%.

[0009] Optionally, when m is 3, the peak intensity of the sodium iron phosphate pyrophosphate positive electrode material corresponding to one of the peaks is 1~4μm, and the mass ratio of the sodium iron phosphate pyrophosphate positive electrode material with a peak intensity of 1~4μm to the sodium iron phosphate pyrophosphate positive electrode material is 10%~30%, the peak intensity of the sodium iron phosphate pyrophosphate positive electrode material corresponding to one of the peaks is 4~7μm, and the mass ratio of the sodium iron phosphate pyrophosphate positive electrode material with a peak intensity of 4~7μm to the sodium iron phosphate pyrophosphate positive electrode material is 10%~30%, the peak intensity of the sodium iron phosphate pyrophosphate positive electrode material corresponding to one of the peaks is 7~10μm, and the mass ratio of the sodium iron phosphate pyrophosphate positive electrode material with a peak intensity of 7~10μm to the sodium iron phosphate pyrophosphate positive electrode material is 40~80%.

[0010] Optionally, the sodium iron phosphate pyrophosphate positive electrode material comprises a core and a carbon layer present on the surface of the core; the chemical formula of the core is Na x Fe y (PO4) z P2O7, wherein 3≤x≤5, 2≤y<4, 1≤z≤3.

[0011] The present invention also provides a method for preparing the sodium iron pyrophosphate positive electrode material as described above, comprising: performing two-fluid spray drying on a mixed slurry comprising a sodium source, an iron source, a phosphorus source, an organic carbon source and an inorganic carbon, during which at least m nozzles are used, and by controlling the gas-liquid ratio of the at least m nozzles, the mixed slurry is spray-dried by the two-fluid spray to form a mixture comprising m groups of powders, wherein the peak intensities of the m groups of powders are different; wherein the D50 of the mixture comprising the m groups of powders is 2-10 μm, and the D100 of the mixture comprising the m groups of powders is less than 25 μm; and the mixture comprising the m groups of powders is sintered in an inert atmosphere to obtain the sodium iron pyrophosphate positive electrode material.

[0012] Optionally, the solid content of the mixed slurry is 20% to 40%; and / or, before the mixed slurry comprising the sodium source, the iron source, the phosphorus source, the organic carbon source and the inorganic carbon is subjected to the two-fluid spray drying, it is first ground to a particle size of the mixed slurry of 0.2 μm to 0.4 μm, and then the ground mixed slurry is subjected to the two-fluid spray drying; and / or, the sodium source comprises one of sodium dihydrogen phosphate, sodium phosphate, sodium carbonate, sodium oxalate, sodium nitrate, sodium chloride, sodium acetate, sodium sulfate, sodium hydroxide, sodium formate, sodium citrate, sodium pyrophosphate, and sodium dihydrogen pyrophosphate. or more; and / or, the phosphorus source includes one or more of sodium dihydrogen phosphate, sodium phosphate, sodium monohydrogen phosphate, phosphoric acid, ammonium dihydrogen phosphate, triammonium phosphate, ferric phosphate, ferric pyrophosphate, pyrophosphoric acid, sodium pyrophosphate, and sodium dihydrogen pyrophosphate; and / or, the iron source includes one or more of iron metal powder, ferric citrate, ferrous citrate, ferric nitrate, ferrous nitrate, ferrous sulfate, ferrous sulfate, ferric chloride, ferrous chloride, ferrous tetroxide, ferrous oxide, ferrous oxalate, ferrous oxalate, ferrous acetate, ferric phosphate, ferric pyrophosphate, and ammonium ferrous sulfate; and / or, the organic carbon source includes One or more of oxalic acid, ascorbic acid, formaldehyde, acetaldehyde, n-butyraldehyde, lactic acid, citric acid, malic acid, oxalic acid, adipic acid, citric acid, soluble starch, polyethylene glycol, aniline, tannic acid, sucrose, and glucose; and / or, the inorganic carbon comprises any one of superconductive carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, and graphene, or a combination of at least two thereof; and / or, during the two-fluid spray drying process, the inlet air temperature is 160-240° C., the outlet air temperature is 85-120° C., and the diameter of the nozzle is 1 mm; and / or, the two-fluid spray During the mist drying process, the ratio of air consumption to liquid spray volume is 30-100; and / or, the sintering process includes: first performing a first gradient sintering at 200-300°C; and then performing a second gradient sintering at 500-600°C; the time for the first gradient sintering is 2-10h; and / or, the time for the second gradient sintering is 2-10h; and / or, the inert atmosphere includes one or more of argon, nitrogen, and hydrogen, the oxygen content in the inert atmosphere is less than 50ppm, and the gas flow rate of the inert atmosphere is 2-10L / min.

[0013] The present invention provides a positive electrode plate, comprising the sodium iron phosphate pyrophosphate positive electrode material as described above or the sodium iron phosphate pyrophosphate positive electrode material obtained according to the preparation method as described above.

[0014] The present invention provides a sodium ion battery, comprising the positive electrode plate as described above.

[0015] The invention provides a sodium iron phosphate pyrophosphate positive electrode material and a preparation method and application thereof. The D50 of the sodium iron phosphate pyrophosphate positive electrode material is 2-10 μm, and the D100 of the sodium iron phosphate pyrophosphate positive electrode material is less than 25 μm; the internal porosity of the sodium iron phosphate pyrophosphate positive electrode material is less than 10%, and the particle size and internal porosity are relatively small, which is helpful to improve the compaction density of the sodium iron phosphate pyrophosphate positive electrode material and improve its capacity (specific capacity, energy density), cycle performance and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is an electron microscope image of the sodium iron phosphate pyrophosphate positive electrode material of Example 1;

[0017] Figure 2 This is a cross-sectional electron microscope image of the sodium iron phosphate pyrophosphate positive electrode material of Example 1;

[0018] Figure 3 This is a particle size distribution diagram of the sodium iron pyrophosphate positive electrode material of Example 1;

[0019] Figure 4 is an X-ray diffraction (XRD) diagram of the sodium iron phosphate pyrophosphate positive electrode material of Example 1;

[0020] Figure 5 The charge and discharge curve of the button cell assembled with the sodium iron phosphate pyrophosphate positive electrode material of Example 1 (the horizontal axis is Capacity (mAh / g), the vertical axis is Voltage (V) vs. Na + / Na);

[0021] Figure 6 The rate performance curve of button cells assembled with the sodium iron phosphate pyrophosphate positive electrode materials of Example 1 (Example 1) and Comparative Example 3;

[0022] Figure 7 The electrical performance diagram of button cells assembled with the sodium iron phosphate pyrophosphate positive electrode materials of Example 1 (Example 1) and Comparative Example 3 after 100 cycles at 1C at room temperature;

[0023] Figure 8 This is the particle size distribution diagram of the sodium iron pyrophosphate positive electrode material of Example 13. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The embodiment of the present invention provides a sodium iron phosphate pyrophosphate positive electrode material, wherein the D50 of the sodium iron phosphate pyrophosphate positive electrode material is 2-10 μm, and the D100 of the sodium iron phosphate pyrophosphate positive electrode material is less than 25 μm; the internal porosity of the sodium iron phosphate pyrophosphate positive electrode material is less than 14%, and the compaction density is greater than 2.17 g / cm 3 .

[0026] According to the inventor's research and analysis: the sodium iron phosphate pyrophosphate positive electrode material of the embodiment of the present invention has a smaller particle size and a smaller internal porosity, which helps to increase the compaction density of the sodium iron pyrophosphate positive electrode material and improve its capacity (specific capacity, energy density), cycle performance and rate performance.

[0027] In some embodiments, there are m peaks in the particle size distribution diagram of the sodium iron phosphate pyrophosphate positive electrode material, and the peak intensities of the sodium iron phosphate pyrophosphate positive electrode material corresponding to the m peaks are not equal, wherein m is an integer greater than or equal to 2, such as 2, 3, 4, and preferably m is 2. That is, the sodium iron phosphate pyrophosphate positive electrode material is formed by blending m groups of secondary particle groups with different particle size distributions, which can fully reduce the internal porosity (internal void ratio of secondary particles) between the particles of the sodium iron phosphate pyrophosphate positive electrode material, which is conducive to improving the compaction density, and improving its capacity, cycle performance and rate performance.

[0028] In the embodiment of the present invention, the peak intensity refers to the abscissa corresponding to the peak value in the particle size distribution diagram, that is, the particle size of the particle.

[0029] Among the above-mentioned m peaks, at least one peak corresponds to a peak intensity of the sodium iron phosphate pyrophosphate positive electrode material of 1~4μm, for example, 1μm, 2μm, 3μm, 4μm or a range consisting of any two thereof, and the mass ratio of the sodium iron phosphate pyrophosphate positive electrode material with a peak intensity of 1~4μm to the sodium iron phosphate pyrophosphate positive electrode material is 10~50%, for example, 10%, 20%, 30%, 40%, 50% or a range consisting of any two thereof; at least one peak corresponds to a peak intensity of the sodium iron phosphate pyrophosphate positive electrode material of 6~10μm, for example, 6μm, 7μm, 8μm or a range consisting of any two thereof. For example, when m is 2, there are 2 peaks in the particle size distribution diagram of the above-mentioned sodium iron phosphate pyrophosphate positive electrode material, one of which corresponds to a peak intensity of 1-4 μm for the sodium iron phosphate pyrophosphate positive electrode material, and the mass ratio of the sodium iron phosphate pyrophosphate positive electrode material with a peak intensity of 1-4 μm to the sodium iron phosphate pyrophosphate positive electrode material is 10%-50%; the other peak corresponds to a peak intensity of 6-10 μm for the sodium iron phosphate pyrophosphate positive electrode material, and the mass ratio of the sodium iron phosphate pyrophosphate positive electrode material with a peak intensity of 6-10 μm to the sodium iron phosphate pyrophosphate positive electrode material is 50%-90%; when m is 3, that is, there are 3 peaks in the particle size distribution diagram of the above-mentioned sodium iron phosphate pyrophosphate positive electrode material. The peak intensity of the sodium iron phosphate pyrophosphate positive electrode material corresponding to one peak is 1~4μm, and the mass ratio of the sodium iron phosphate pyrophosphate positive electrode material with a peak intensity of 1~4μm to the sodium iron phosphate pyrophosphate positive electrode material is 10%~30%, the peak intensity of the sodium iron phosphate pyrophosphate positive electrode material corresponding to one peak is 4~7μm, and the mass ratio of the sodium iron phosphate pyrophosphate positive electrode material with a peak intensity of 4~7μm to the sodium iron phosphate pyrophosphate positive electrode material is 10%~30%, and the peak intensity of the sodium iron phosphate pyrophosphate positive electrode material corresponding to another peak is 7~10μm, and the mass ratio of the sodium iron phosphate pyrophosphate positive electrode material with a peak intensity of 7~10μm to the sodium iron phosphate pyrophosphate positive electrode material is 40~80%. The secondary particles with different particle size distributions are fully blended to fully reduce the internal porosity between the above-mentioned sodium iron phosphate pyrophosphate positive electrode material particles, increase the compaction density, and improve the capacity, cycle performance and rate performance of the battery.

[0030] In some embodiments, the sodium iron pyrophosphate positive electrode material includes an inner core and a carbon layer present on the surface of the inner core. The primary particles are tightly aggregated under the action of the van der Waals force of the carbon layer to form compact secondary particles, which helps to reduce the internal porosity of the sodium iron pyrophosphate positive electrode material, increase the compaction density, and improve the capacity, cycle performance and rate performance of the battery.

[0031] The chemical formula of the above core can be Na x Fe y (PO4) z P2O7, wherein 3≤x≤5, 2≤y<4, 1≤z≤3.

[0032] In some embodiments, the particle size of the primary particles of the sodium iron phosphate pyrophosphate positive electrode material is less than 100 nm.

[0033] The particle size of the primary particles of the sodium iron pyrophosphate positive electrode material can be measured by the following process: after observing 200 primary particles in the field of view of 10.0K magnification under a scanning electron microscope, the average particle size is calculated to obtain the particle size of the primary particles.

[0034] In some embodiments, the compaction density of the sodium iron phosphate pyrophosphate positive electrode material is greater than or equal to 2.05 g / cm 3 .

[0035] An embodiment of the present invention also provides a method for preparing the above-mentioned sodium iron pyrophosphate positive electrode material, comprising: performing two-fluid spray drying on a mixed slurry including a sodium source, an iron source, a phosphorus source, an organic carbon source and an inorganic carbon, during which at least m nozzles are used, and by controlling the gas-liquid ratio of the at least m nozzles, the mixed slurry is spray-dried by the two-fluid spray to form a mixture including m groups of powders, and the peak intensities of the m groups of powders are different; wherein the D50 of the mixture including the m groups of powders is 2-10 μm, and the D100 of the mixture including the m groups of powders is less than 25 μm; and the mixture including the m groups of powders is sintered in an inert atmosphere to obtain the above-mentioned sodium iron pyrophosphate positive electrode material.

[0036] According to the inventor's research and analysis: m groups of powders with different peak intensities can be prepared simultaneously through two-fluid spray drying, and the m groups of powders are evenly mixed in proportion to form a mixture. The mixture is sintered to obtain m groups of secondary particle groups with different peak intensities, and the m groups of secondary particle groups are evenly mixed to form a sodium iron phosphate pyrophosphate positive electrode material. The blending of the m groups of secondary particle groups with different particle sizes can fully reduce the void ratio between the particles of the sodium iron phosphate pyrophosphate positive electrode material, reduce the internal porosity of the sodium iron phosphate pyrophosphate positive electrode material, and increase the compaction density; at the same time, by adding inorganic carbon, the conductivity (electrical conductivity) of the sodium iron phosphate pyrophosphate positive electrode material can be improved, and it can also Reducing the amount of organic carbon source used and inhibiting the production of pores in the organic carbon source during sintering (high temperature decomposition) is beneficial to reducing the internal porosity of the sodium iron phosphate pyrophosphate cathode material. The strong van der Waals force between inorganic carbon (inorganic carbon structure) can also be used to tightly aggregate the primary particles (polyanion material) to form compact secondary particles, thereby reducing the internal porosity of the sodium iron phosphate pyrophosphate cathode material, increasing the compaction density, and improving the capacity, cycle performance, and rate performance. In addition, the particle size distribution of the sodium iron phosphate pyrophosphate cathode material particles can be controlled by granulating by a two-fluid spray method, so that its D50 can be freely adjusted in the range of 2~10μm, while ensuring that its D100 (maximum particle size D max ) is less than 25μm.

[0037] Therefore, the preparation method provided in the embodiment of the present invention can prepare sodium iron pyrophosphate positive electrode material (NFPP material) with stable and controllable secondary particle size, low porosity, high compaction density, high cycle performance and high rate performance. In addition, the operation process of the preparation method is simple, green and environmentally friendly, which is conducive to large-scale industrial expansion and has high industrial applicability.

[0038] The sodium source may include one or more of sodium dihydrogen phosphate, sodium phosphate, sodium carbonate, sodium oxalate, sodium nitrate, sodium chloride, sodium acetate, sodium sulfate, sodium hydroxide, sodium formate, sodium citrate, sodium pyrophosphate, and sodium dihydrogen pyrophosphate. The phosphorus source may include one or more of sodium dihydrogen phosphate, sodium phosphate, sodium monohydrogen phosphate, phosphoric acid, ammonium dihydrogen phosphate, triammonium phosphate, ferric phosphate, ferric pyrophosphate, pyrophosphoric acid, sodium pyrophosphate, and sodium dihydrogen pyrophosphate. The iron source may include one or more of iron metal powder, ferric citrate, ferrous citrate, ferric nitrate, ferrous nitrate, ferrous sulfate, ferrous sulfate, ferric chloride, ferrous chloride, ferrous tetroxide, ferrous oxide, ferrous oxalate, ferrous oxalate, ferrous acetate, ferric phosphate, ferric pyrophosphate, and ammonium ferrous sulfate.

[0039] The carbon and inorganic carbon formed by sintering (oxygen-free high-temperature decomposition) of the organic carbon source in an inert atmosphere form a carbon layer in the sodium iron pyrophosphate positive electrode material, and the carbon layer exists (covers) on the inner core surface of the sodium iron pyrophosphate positive electrode material.

[0040] The mass ratio of the organic carbon source to the sodium iron phosphate pyrophosphate positive electrode material may be 5%-10%, such as 5%; the mass ratio of the inorganic carbon to the sodium iron phosphate pyrophosphate positive electrode material may be 0.1%-1%, such as 0.5%.

[0041] In some embodiments, the organic carbon source includes one or more of oxalic acid, ascorbic acid, formaldehyde, acetaldehyde, n-butyraldehyde, lactic acid, citric acid, malic acid, oxalic acid, adipic acid, citric acid, soluble starch, polyethylene glycol, aniline, tannic acid, sucrose, and glucose.

[0042] In some embodiments, the inorganic carbon (inorganic amorphous carbon) includes any one of Super-P (SP), acetylene black, Ketjen black, carbon fiber, carbon nanotubes and graphene, or a combination of at least two thereof. The strong van der Waals force between the structures of the inorganic carbon causes the primary particles to be tightly aggregated, thereby reducing the internal porosity of the sodium iron pyrophosphate positive electrode material, increasing its compaction density, and improving the capacity, cycle performance and rate performance.

[0043] The above raw materials are widely distributed, cheap and easy to obtain, which helps to reduce production costs.

[0044] In some embodiments, a mixed slurry comprising a sodium source, an iron source, a phosphorus source, an organic carbon source and an inorganic carbon can be obtained by a process comprising the following steps: the sodium source, the iron source, the phosphorus source, the organic carbon source and the inorganic carbon (inorganic carbon source) are respectively weighed according to a stoichiometric ratio, and dispersed evenly in deionized water or a mixture of anhydrous ethanol and deionized water to obtain a mixed slurry comprising a sodium source, an iron source, a phosphorus source, an organic carbon source and an inorganic carbon.

[0045] The volume ratio of the anhydrous ethanol to the deionized water may be (4-6):(94-96), for example, 4:96, 5:95, 6:94 or a range consisting of any two thereof, preferably 5:95.

[0046] In some embodiments, the solid content of the mixed slurry including the sodium source, the iron source, the phosphorus source, the organic carbon source and the inorganic carbon is 20% to 40%, for example, 20%, 25%, 30%, 35%, 40% or a range consisting of any two of them, preferably 25% to 30%, which helps to improve the compaction density of the sodium iron phosphate pyrophosphate positive electrode material. The reason for this is that if the solid content of the mixed slurry is too high, the effect of the two-fluid spraying will be reduced, while if the solid content of the mixed slurry is too low, the moisture content of the mixed slurry will be too high. During the two-fluid spraying process, a large amount of water evaporates, which increases the internal pores of the sodium iron phosphate pyrophosphate positive electrode material and reduces its compaction density. Therefore, by controlling the solid content of the slurry to 20% to 40%, it helps to improve the compaction density of the sodium iron phosphate pyrophosphate positive electrode material and improve its capacity, cycle performance and rate performance.

[0047] Before the mixed slurry including the sodium source, iron source, phosphorus source, organic carbon source and inorganic carbon is subjected to two-fluid spray drying, it can be first ground to a particle size of 0.2μm~0.4μm, and then the ground mixed slurry is subjected to two-fluid spray drying, which is helpful to improve the compaction density of the sodium iron pyrophosphate positive electrode material and improve its capacity, cycle performance and rate performance. The reason is analyzed as follows: if the particle size of the mixed slurry is too small, the viscosity of the mixed slurry is too high, which will reduce the effect of the two-fluid spray, and if the particle size of the mixed slurry is too large, the phase formation effect of the mixed slurry after the two-fluid spray will be worse, which is not conducive to improving the compaction density of the sodium iron pyrophosphate positive electrode material. Therefore, by controlling the particle size of the mixed slurry to 0.2μm~0.4μm, it is helpful to improve the compaction density of the sodium iron pyrophosphate positive electrode material and improve its capacity, cycle performance and rate performance.

[0048] In a specific implementation, the grinding can be performed in a sand mill. For example, the mixed slurry is ground in a sand mill by wet sand grinding for 2 to 10 hours until the particle size of the mixed slurry is 0.2 μm to 0.4 μm.

[0049] In the process of two-fluid spray drying of a mixed slurry including a sodium source, an iron source, a phosphorus source, an organic carbon source and an inorganic carbon, a multi-channel multi-nozzle device (a sprayer) can be used. By adjusting the gas-liquid ratio of different nozzles (the ratio of air consumption to liquid spray amount Qa / Qq), different nozzles can discharge secondary particles of different particle sizes. The blending ratio of secondary particles of different particle sizes can also be controlled by adjusting the multi-channel feed flow rate (feed amount of different nozzles), and the two particles of different particle sizes are uniformly mixed in the sprayer. After discharge, a mixture of particles of different particle sizes (the above m groups of powders) can be collected to obtain a uniform blend (realizing secondary granulation), that is, particles of different particle size distributions (the above m groups of powders) can be prepared simultaneously through the two-fluid spray drying and these particles can be fully mixed.

[0050] In some embodiments, during the two-fluid spray drying process, at least m nozzles are used, and by controlling the gas-liquid ratio (the ratio of air consumption to liquid spray amount Qa / Qq) of the at least m nozzles, the mixed slurry is spray-dried by the two-fluid spray to form a mixture including m groups of powders, and the peak intensities of the m groups of powders are different; wherein the D50 of the mixture including the m groups of powders is 2-10μm, and the D100 (maximum particle size Dmax) of the mixture including the m groups of powders is less than 25μm. During the above two-fluid spray drying process, m groups of powders with different particle size distributions can be prepared at the same time, and the m groups of powders are fully mixed to form a mixture including the m groups of powders.

[0051] By adjusting the ratio of air consumption to liquid spray volume (gas-liquid ratio of the nozzle), the particle size (particle size) of the particles after spraying can be controlled. The larger the gas-liquid ratio, the smaller the particle size of the particles, and the smaller the gas-liquid ratio, the larger the particle size of the particles. In some embodiments, during the above-mentioned two-fluid spray drying process, the ratio of air consumption to liquid spray volume (gas-liquid ratio of the nozzle) is 10-200, which is convenient for controlling the D50 of the sodium iron pyrophosphate positive electrode material to 2-10μm, which is beneficial to improve the compaction density of the sodium iron pyrophosphate positive electrode material, and improve its capacity, cycle performance and rate performance.

[0052] In some embodiments, during the two-fluid spray drying process, the inlet air temperature is 160-240°C, for example, 160°C, 180°C, 200°C, 220°C, 240°C or a range consisting of any two thereof, the outlet air temperature is 85-120°C, for example, 85°C, 95°C, 100°C, 120°C or a range consisting of any two thereof, and the nozzle diameter is 1-5μm, for example, 1μm, 2μm, 3μm, 4μm, 5μm or a range consisting of any two thereof.

[0053] Furthermore, in the above two-fluid spray drying process, the blower frequency can be 35±1 Hz, the induced draft fan frequency can be 40±1 Hz, and the atomizer frequency can be 45±1 Hz.

[0054] In the above two-fluid spray drying process, the feeding frequency can be adjusted according to the outlet air temperature so that the mass ratio of powders with different particle size distributions can reach the expected value.

[0055] By sintering (calcining) the above mixture including the m group powder in an inert atmosphere, a sodium iron pyrophosphate positive electrode material with low internal porosity, high compaction density, high capacity, high cycle performance and high rate performance can be obtained.

[0056] In some embodiments, the sintering process includes: first performing a first gradient sintering at 200-300° C.; and then performing a second gradient sintering at 500-600° C. Exemplarily, the temperature of the first gradient sintering is 200° C., 220° C., 250° C., 280° C., 300° C., or a range consisting of any two thereof, and the temperature of the second gradient sintering is 500° C., 520° C., 550° C., 580° C., 600° C., or a range consisting of any two thereof.

[0057] Further, during the first gradient sintering process, the temperature can be raised to the sintering temperature at a heating rate of 3 to 6°C / min, such as 3°C / min, 5°C / min, 6°C / min, or any combination of two thereof; during the second gradient sintering process, the temperature can be raised to the sintering temperature at a heating rate of 3 to 6°C / min, such as 3°C / min, 5°C / min, 6°C / min, or any combination of two thereof;

[0058] The first gradient sintering time may be 2-10 h, for example, 2 h, 3 h, 5 h, 8 h, 10 h or a range consisting of any two thereof.

[0059] The second gradient sintering time may be 2-10 h, for example, 2 h, 3 h, 5 h, 8 h, 10 h or a range consisting of any two thereof.

[0060] The inert atmosphere may include one or more of argon, nitrogen, and hydrogen. The oxygen content in the inert atmosphere may be less than 50 ppm, and the gas flow rate of the inert atmosphere may be 2-10 L / min.

[0061] In some embodiments, the inert atmosphere includes nitrogen and hydrogen, wherein the volume ratio of nitrogen to hydrogen is (94-96):(4-6), for example, 94:6, 95:5, 96:4 or a range of any two thereof.

[0062] An embodiment of the present invention further provides a positive electrode plate, comprising the above-mentioned sodium iron phosphate pyrophosphate positive electrode material.

[0063] The positive electrode sheet of the embodiment of the present invention specifically includes a positive electrode current collector and a positive electrode active layer formed by the above-mentioned sodium iron phosphate pyrophosphate positive electrode material and arranged on the surface of the positive electrode current collector.

[0064] When preparing the positive electrode sheet, for example, the sodium iron phosphate pyrophosphate positive electrode material of the embodiment of the present invention, the conductive agent and the binder can be dispersed in an appropriate amount of N-methylpyrrolidone (NMP) solvent, and the mixture is fully stirred to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector, and the positive electrode sheet is obtained after drying, rolling and cutting. In a specific embodiment, the positive electrode active layer includes 70-99wt% of sodium iron phosphate pyrophosphate positive electrode material, 0.5-15wt% of conductive agent, and 0.5-15wt% of binder according to the mass percentage, and further includes 80-98wt% of sodium iron phosphate pyrophosphate positive electrode material, 1-10 wt% of conductive agent, and 1-10wt% of binder.

[0065] Among them, the material of the positive electrode current collector can be at least one of aluminum foil and nickel foil; the conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber; the binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, and polyurethane.

[0066] An embodiment of the present invention further provides a sodium ion battery, comprising the above-mentioned positive electrode plate.

[0067] It is conceivable that the sodium ion battery of the embodiment of the present invention includes, in addition to the above-mentioned positive electrode plate, a negative electrode plate, an electrolyte and a separator.

[0068] The embodiments of the present invention do not strictly limit the negative electrode active material in the negative electrode sheet, and may be a negative electrode active material commonly used in current sodium ion batteries, such as at least one of hard carbon, soft carbon, titanium-based materials, metal oxides and sulfides.

[0069] The embodiment of the present invention does not strictly limit the selection of the electrolyte, and may include one or more of the solvents commonly used in the current sodium ion battery electrolyte, and the electrolytes commonly used in the current sodium ion electrolyte, for example: the solvent may be ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, ethyl methyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, sulfolane, γ-butyrolactone, etc.; the electrolyte may be, for example, one or more of sodium hexafluorophosphate, sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, and sodium fluorotrifluoromethylsulfonylimide.

[0070] The embodiment of the present invention does not strictly limit the material selection of the diaphragm, and it can be a diaphragm material commonly used in sodium ion batteries, such as a polypropylene diaphragm (PP), a polyethylene diaphragm (PE), a polypropylene / polyethylene double-layer composite film (PP / PE), a polyimide electrospinning diaphragm (PI), a polypropylene / polyethylene / polypropylene three-layer composite film (PP / PE / PP), a cellulose non-woven fabric diaphragm, and a diaphragm with a ceramic coating.

[0071] When preparing sodium-ion batteries, the positive electrode sheet, separator and negative electrode sheet are wound or stacked to obtain a bare cell, and the bare cell is packaged in a pre-stamped aluminum-plastic film bag. After the packaged battery is dried at 85°C, the electrolyte is injected into the dry battery. After the battery is shelved, formed and sealed for the second time, the preparation of the sodium-ion battery is completed.

[0072] The present invention is described in more detail below through specific embodiments.

[0073] Example 1

[0074] This embodiment provides a method for preparing a sodium iron phosphate pyrophosphate positive electrode material, comprising:

[0075] Weigh iron oxide, iron phosphate, sodium carbonate, glucose, and Ketjen black respectively and dissolve them in deionized water, wherein the molar ratio of iron oxide, iron phosphate, and sodium carbonate is 4:3:4, the mass ratio of glucose to the mass ratio of sodium ferric pyrophosphate positive electrode material is 5%, and the mass ratio of Ketjen black to the mass ratio of sodium ferric pyrophosphate positive electrode material is 0.5%, and stir and mix them uniformly at room temperature to obtain a mixed slurry including a sodium source, an iron source, a phosphorus source, an organic carbon source, and an inorganic carbon, wherein the solid content of the mixed slurry is controlled at 30%;

[0076] The mixed slurry is transferred to a sand mill and ground for 5 hours, and the slurry particle size is controlled at 0.2μm-0.4μm;

[0077] The mixed slurry is subjected to two-fluid spray drying using a dual-channel two-fluid spray dryer. During the two-fluid spray drying process, two nozzles are used, each with a nozzle diameter of 5 mm. The gas-liquid ratio Qa / Qq of one nozzle is controlled to be 50, so that the peak intensity of the powder obtained by the nozzle is 8 μm. The gas-liquid ratio Qa / Qq of the other nozzle is controlled to be 100, so that the peak intensity of the powder obtained by the nozzle is 2 μm. The feed amounts of the two nozzles are controlled so that the mass ratio of the powder with a peak intensity of 8 microns to the powder with a peak intensity of 2 microns is 2:1, so as to form a mixture. The frequency of the blower is (35±1) Hz, the frequency of the induced draft fan is (40±1) Hz, the frequency of the atomizer is (45±1) Hz, the air inlet temperature is controlled to be 190±2°C, and the air outlet temperature is 110±2°C.

[0078] The above mixture was sintered in a nitrogen / hydrogen (volume ratio 95:5) atmosphere, first heated to 220°C at a rate of 5°C / min for a first gradient sintering for 5 hours, and then heated to 510°C at a rate of 5°C / min for a second gradient sintering for 8 hours to obtain sodium iron pyrophosphate positive electrode material (Na4Fe3(PO4)2P2O7).

[0079] Referring to the process of Example 1, the sodium iron phosphate pyrophosphate positive electrode materials of Examples 2 to 14 and Comparative Examples 1 to 3 were prepared respectively.

[0080] The mass ratio of the sodium source, iron source, phosphorus source, organic carbon source to the positive electrode material (mass ratio of the organic carbon source to the positive electrode material), the mass ratio of the inorganic carbon to the positive electrode material (mass ratio of the inorganic carbon to the positive electrode material), the solid content of the mixed slurry, the particle size of the mixed slurry, etc. of each embodiment and comparative example are summarized in Table 1;

[0081] The air inlet temperature, air outlet temperature, number of nozzles, diameter (diameter of the nozzle), gas-liquid ratio (Qa / Qq) (gas-liquid ratio of nozzle discharge), m, particle size distribution peak intensity and mass ratio of the m group of powders in the mixture, temperature and time of the first gradient sintering, temperature and time of the second gradient sintering, inert atmosphere, etc. of each embodiment and comparative example are summarized in Table 2;

[0082] Table 1

[0083]

[0084] Table 2

[0085]

[0086] Test Example 1

[0087] 1. The following parameters of the above embodiments and comparative examples were tested:

[0088] 1) D50 and D100 of sodium iron pyrophosphate cathode material: Use a laser particle size analyzer to analyze the particle size of the sample through the spatial distribution of diffraction or scattering;

[0089] 2) Internal porosity of sodium iron pyrophosphate cathode material: The cross-section of the sodium iron pyrophosphate cathode material was measured using a profiler and a scanning electron microscope, and the porosity of the material was calculated using ImageJ image processing and analysis software;

[0090] 3) Chemical composition of sodium iron pyrophosphate positive electrode material: The test was completed using an inductively coupled plasma emission spectrometer (ICP), and the chemical formula of the sodium iron pyrophosphate positive electrode material is recorded in Table 3;

[0091] 4) Compaction density of sodium iron pyrophosphate positive electrode material: The compaction density under 3 tons of pressure was tested using the battery powder automatic compaction density tester UTM7105;

[0092] 5) Scanning electron micrograph of sodium iron phosphate pyrophosphate positive electrode material: The scanning electron micrograph of the sodium iron phosphate pyrophosphate positive electrode material of Example 1 is as follows: Figure 1 As shown, the cross-sectional electron microscope image of the sodium iron phosphate pyrophosphate positive electrode material of Example 1 is as follows Figure 2 As shown;

[0093] 6) Particle size distribution diagram of sodium iron phosphate pyrophosphate positive electrode material: The particle size distribution diagram of the sodium iron phosphate pyrophosphate positive electrode material of Example 1 is as follows Figure 3 As shown, the particle size distribution diagram of the sodium iron phosphate pyrophosphate positive electrode material of Example 13 is as follows Figure 8 As shown;

[0094] 7) X-ray diffraction (XRD) diagram of sodium iron phosphate pyrophosphate positive electrode material: The X-ray diffraction (XRD) diagram of the sodium iron phosphate pyrophosphate positive electrode material of Example 1 is as follows: Figure 4 As shown;

[0095] 9) Purity of the sodium ferric pyrophosphate (NFPP) phase of the sodium ferric pyrophosphate positive electrode material: The XRD results were refined using TOPAS.

[0096] 2. Test results

[0097] Table 3

[0098]

[0099] Data Analysis:

[0100] The primary particle size of the sodium iron phosphate pyrophosphate positive electrode material of Comparative Example 1 is relatively large and the conductivity is relatively poor;

[0101] also, Figure 1This is an electron microscope image of the sodium iron phosphate pyrophosphate positive electrode material of Example 1, from which it can be seen that the sodium iron phosphate pyrophosphate positive electrode material particles are spherical in shape and the particle size is controllable; Figure 2 This is a cross-sectional electron micrograph of the sodium iron phosphate pyrophosphate positive electrode material of Example 1. It can be seen that there are no obvious macropores inside the sodium iron phosphate pyrophosphate positive electrode material and the solidity is high. The electron micrographs and cross-sectional electron micrographs of the sodium iron phosphate pyrophosphate positive electrode materials of other examples are similar to those of Example 1.

[0102] Figure 3 The particle size distribution diagram of the sodium iron phosphate pyrophosphate positive electrode material of Example 1 shows that the sodium iron phosphate pyrophosphate positive electrode material particles have two peaks in the particle size distribution diagram, and the peaks correspond to the sodium iron phosphate pyrophosphate positive electrode material particles with D50 of 3 μm and 8 μm respectively. The particle size distribution diagrams of the sodium iron phosphate pyrophosphate positive electrode materials of Examples 2-19 are similar to that of Example 1.

[0103] Figure 4 The X-ray diffraction (XRD) diagram of the sodium iron phosphate pyrophosphate positive electrode material of Example 1 shows that the NFPP phase purity of the sodium iron phosphate pyrophosphate positive electrode material is 95.4%, and the NFP phase accounts for 3.1%. The X-ray diffraction (XRD) diagrams of the sodium iron phosphate pyrophosphate positive electrode materials of other examples are similar to that of Example 1.

[0104] Figure 5 The charge and discharge curve of the button battery assembled with the sodium iron phosphate pyrophosphate positive electrode material of Example 1 (the horizontal axis is Capacity (mAh / g), i.e., capacity, and the vertical axis is Voltage (V) vs. Na + / Na, that is, voltage), Figure 6 The rate performance curve of button cells assembled with the sodium iron phosphate pyrophosphate positive electrode materials of Example 1 (Example 1) and Comparative Example 3 is shown in FIG. Figure 7 The electrical performance graphs of button-type batteries assembled with sodium iron phosphate pyrophosphate positive electrode materials of Example 1 (Example 1) and Comparative Example 3 after 100 cycles at 1C at room temperature; it can be seen that the button-type battery assembled with sodium iron phosphate pyrophosphate positive electrode materials of Example 1 has high discharge specific capacity, high rate performance and high cycle performance. The charge and discharge curves of button-type batteries assembled with sodium iron phosphate pyrophosphate positive electrode materials of other examples are similar to those of Example 1.

[0105] Test Example 2

[0106] The sodium iron phosphate pyrophosphate positive electrode materials of the embodiment and the comparative example are respectively made into positive electrode sheets, and then assembled with negative electrode sheets, electrolytes and separators according to the following method to obtain button batteries. The method includes:

[0107] The sodium iron phosphate pyrophosphate positive electrode material was mixed with carbon black conductive agent and polyvinylidene fluoride in a mass ratio of 9:0.5:0.5, and then N-methylpyrrolidone solvent was added to prepare a slurry; then, the slurry was coated on aluminum foil and rolled to obtain a surface density of 5.5 g / cm 3 The positive electrode sheet is baked in a vacuum drying oven at 120°C for 12h to obtain a positive electrode sheet; metallic sodium is used as a counter electrode; glass fiber is used as a separator; the electrolyte includes EC (ethylene carbonate): DMC (dimethyl carbonate) in a mass ratio of 1:1, and also includes NaClO4 and FEC (fluoroethylene carbonate), wherein the concentration of NaClO4 in the electrolyte is 1 mol / L, and the mass percentage of FEC is 5%; hard carbon is used as the negative electrode; and a button battery is assembled in an argon glove box.

[0108] The reversible capacity, capacity retention rate at 10C and capacity retention rate after 100 cycles at 1C of the button cell were tested:

[0109] At 25°C, charge to 3.75V at a constant current of 0.2C, then charge to 3.75V at a constant voltage of 0.05C, then let stand for 2 minutes, discharge to 1.5V at a discharge rate of 0.2C, and let stand for 2 minutes; then repeat this charge and discharge cycle 100 times at 1C; measure the reversible capacity, the discharge capacity Q1 at the first cycle and the discharge capacity Q at the 100th cycle 100 The capacity retention rate after 100 cycles of 1C is calculated as Q according to the following formula: 100 / Q1*100%);

[0110] At 25°C, charge to 3.75V at a constant current of 0.2C, then charge to 3.75V at a constant voltage of 0.05C, then let stand for 2 minutes, discharge to 1.5V at a discharge rate of 0.2C, and let stand for 2 minutes; then perform charge and discharge cycles at 10C according to the above method; measure the discharge capacity and charge capacity, calculate the ratio of the discharge capacity to the charge capacity, and obtain the capacity retention rate at 10C.

[0111] The results are shown in Table 4;

[0112] Table 4

[0113]

[0114] Data Analysis:

[0115] Compared with Comparative Example 1, the reversible capacity and capacity retention rate of each embodiment are better, which verifies that by adding inorganic carbon, the conductivity (electrical conductivity) of the sodium iron phosphate pyrophosphate positive electrode material can be improved, and the amount of organic carbon source used can be reduced, and the production of pores by the organic carbon source under sintering (high temperature decomposition) is inhibited, which is beneficial to reduce the internal porosity of the sodium iron phosphate pyrophosphate positive electrode material. The strong van der Waals force between inorganic carbon (inorganic carbon structure) can also be used to make the primary particles (polyanion material) tightly aggregated to form compact secondary particles, thereby reducing the internal porosity of the sodium iron phosphate pyrophosphate positive electrode material, increasing the compaction density, and improving the capacity, cycle performance and rate performance;

[0116] Compared with Comparative Examples 2 and 3, the reversible capacity and capacity retention rate of each embodiment are better, which verifies that the above-mentioned sodium iron phosphate pyrophosphate positive electrode material is formed by blending m groups of secondary particle groups with different particle size distributions, which can fully reduce the internal porosity (internal porosity of secondary particles) between the particles of the above-mentioned sodium iron phosphate pyrophosphate positive electrode material, which is beneficial to increase the compaction density and improve its capacity, cycle performance and rate performance.

[0117] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A sodium iron phosphate pyrophosphate positive electrode material, characterized in that: The D50 of the sodium iron phosphate pyrophosphate positive electrode material is 2-10 μm, and the D100 of the sodium iron phosphate pyrophosphate positive electrode material is less than 25 μm; The internal porosity of the sodium iron phosphate pyrophosphate positive electrode material is less than 14%, and the compaction density is greater than 2.17g / cm 3 .

2. The sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that There are m peaks in the particle size distribution diagram of the sodium iron phosphate pyrophosphate positive electrode material, and the peak intensities of the sodium iron phosphate pyrophosphate positive electrode material corresponding to the m peaks are not equal, wherein m is an integer greater than or equal to 2.

3. The sodium iron phosphate pyrophosphate positive electrode material according to claim 2, characterized in that Among the m peaks, at least one peak corresponds to the peak intensity of the sodium iron phosphate pyrophosphate positive electrode material of 1~4μm, and the mass ratio of the sodium iron phosphate pyrophosphate positive electrode material with a peak intensity of 1~4μm to the sodium iron phosphate pyrophosphate positive electrode material is 10~50%; at least one peak corresponds to the peak intensity of the sodium iron phosphate pyrophosphate positive electrode material of 6~10μm.

4. The sodium iron phosphate pyrophosphate positive electrode material according to claim 3, characterized in that When m is 2, the peak intensity of the sodium iron phosphate pyrophosphate positive electrode material corresponding to one of the peaks is 1~4μm, and the mass ratio of the sodium iron phosphate pyrophosphate positive electrode material with a peak intensity of 1~4μm to the sodium iron phosphate pyrophosphate positive electrode material is 10%~50%; the peak intensity of the sodium iron phosphate pyrophosphate positive electrode material corresponding to the other peak is 6~10μm, and the mass ratio of the sodium iron phosphate pyrophosphate positive electrode material with a peak intensity of 6~10μm to the sodium iron phosphate pyrophosphate positive electrode material is 50%~90%.

5. The sodium iron phosphate pyrophosphate positive electrode material according to claim 3, characterized in that When m is 3, the peak intensity of the sodium iron phosphate pyrophosphate positive electrode material corresponding to one of the peaks is 1~4μm, and the mass ratio of the sodium iron phosphate pyrophosphate positive electrode material with a peak intensity of 1~4μm to the sodium iron phosphate pyrophosphate positive electrode material is 10%~30%, the peak intensity of the sodium iron phosphate pyrophosphate positive electrode material corresponding to one of the peaks is 4~7μm, and the mass ratio of the sodium iron phosphate pyrophosphate positive electrode material with a peak intensity of 4~7μm to the sodium iron phosphate pyrophosphate positive electrode material is 10%~30%, the peak intensity of the sodium iron phosphate pyrophosphate positive electrode material corresponding to one of the peaks is 7~10μm, and the mass ratio of the sodium iron phosphate pyrophosphate positive electrode material with a peak intensity of 7~10μm to the sodium iron phosphate pyrophosphate positive electrode material is 40~80%.

6. The sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that The sodium iron phosphate pyrophosphate positive electrode material comprises a core and a carbon layer present on the surface of the core; The chemical formula of the core is Na x Fe y (PO4) z P2O7, Among them, 3≤x≤5, 2≤y<4, 1≤z≤3.

7. A method for preparing the sodium iron phosphate pyrophosphate positive electrode material according to any one of claims 1 to 6, characterized in that: include: A mixed slurry including a sodium source, an iron source, a phosphorus source, an organic carbon source and an inorganic carbon is subjected to two-fluid spray drying. During the two-fluid spray drying, at least m nozzles are used, and the gas-liquid ratio of the at least m nozzles is controlled so that the mixed slurry is subjected to the two-fluid spray drying to form a mixture including m groups of powders, and the peak intensities of the m groups of powders are different; wherein the D50 of the mixture including the m groups of powders is 2-10 μm, and the D100 of the mixture including the m groups of powders is less than 25 μm; The mixture including the m group of powders is sintered in an inert atmosphere to obtain the sodium iron phosphate pyrophosphate positive electrode material.

8. The preparation method according to claim 7, characterized in that: The solid content of the mixed slurry is 20% to 40%; and / or, before the mixed slurry comprising the sodium source, the iron source, the phosphorus source, the organic carbon source and the inorganic carbon is subjected to the two-fluid spray drying, the mixed slurry is first ground to a particle size of 0.2 μm to 0.4 μm, and then the ground mixed slurry is subjected to the two-fluid spray drying; And / or, the sodium source includes one or more of sodium dihydrogen phosphate, sodium phosphate, sodium carbonate, sodium oxalate, sodium nitrate, sodium chloride, sodium acetate, sodium sulfate, sodium hydroxide, sodium formate, sodium citrate, sodium pyrophosphate, and sodium dihydrogen pyrophosphate; And / or, the phosphorus source includes one or more of sodium dihydrogen phosphate, sodium phosphate, sodium monohydrogen phosphate, phosphoric acid, ammonium dihydrogen phosphate, triammonium phosphate, ferric phosphate, ferric pyrophosphate, pyrophosphoric acid, sodium pyrophosphate, and sodium dihydrogen pyrophosphate; And / or, the iron source includes one or more of iron metal powder, ferric citrate, ferrous citrate, ferric nitrate, ferrous nitrate, ferric sulfate, ferrous sulfate, ferric chloride, ferrous chloride, ferrous tetroxide, ferrous oxide, ferrous oxide, ferrous oxalate, ferrous oxalate, ferric acetate, ferric phosphate, ferric pyrophosphate, and ammonium ferrous sulfate; and / or, the organic carbon source comprises one or more of oxalic acid, ascorbic acid, formaldehyde, acetaldehyde, n-butyraldehyde, lactic acid, citric acid, malic acid, oxalic acid, adipic acid, citric acid, soluble starch, polyethylene glycol, aniline, tannic acid, sucrose, and glucose; And / or, the inorganic carbon includes any one or a combination of at least two of superconductive carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes and graphene; and / or, during the two-fluid spray drying process, the air inlet temperature is 160-240° C., the air outlet temperature is 85-120° C., and the nozzle diameter is 1-5 mm; and / or, during the two-fluid spray drying process, the ratio of air consumption to liquid spray amount is 30-100; And / or, the sintering process includes: firstly performing a first gradient sintering at 200-300° C.; and then performing a second gradient sintering at 500-600° C.; The first gradient sintering time is 2 to 10 hours; And / or, the second gradient sintering time is 2 to 10 hours; And / or, the inert atmosphere includes one or more of argon, nitrogen, and hydrogen, the oxygen content in the inert atmosphere is less than 50 ppm, and the gas flow rate of the inert atmosphere is 2-10 L / min.

9. A positive electrode sheet, characterized in that: The invention comprises the sodium iron phosphate pyrophosphate positive electrode material according to any one of claims 1 to 6 or the sodium iron phosphate pyrophosphate positive electrode material obtained according to the preparation method according to claim 7 or 8.

10. A sodium ion battery, characterized in that: Including the positive electrode sheet as described in claim 9.

Citation Information

Cited By

  • High-solid-degree composite sodium ferric phosphate positive electrode material, preparation method thereof and battery

    CN121063508A

  • Sodium iron phosphate-pyrophosphate positive electrode material, and preparation method therefor and use thereof

    WO2026124205A1